Obstetric outcomes in patients who have undergone excisional treatment for high-grade cervical squamous intra-epithelial neoplasia. (May 2019) - Maina, Giovanni; Ribaldone, Raffaella; Danese, Saverio; Lombardo, Valentina; Cavagnetto, Cristina; Plazzotta, Claudio; Surico, Daniela
Abstract: Objective: To evaluate the relationships between excisional treatment for high-grade cervical intra-epithelial neoplasia (CIN2+) and obstetric outcomes in terms of preterm delivery risk, premature rupture of membrane (PROM) and type of delivery, and between pre-term delivery and the type of excisional technique (radio frequency excision, laser conization). Methods: This was a retrospective study of the obstetric outcomes of 2316 women aged 25–45 years who underwent excisional treatment for CIN2+ at the Obstetric and Gynecological Clinic of Ospedale Maggiore della Carità in Novara and at the Obstetric and Gynecological Department of Ospedale Sant'Anna in Torino in the period 2005–2014 and were evaluated until April 2016, and 57, 937 untreated women of the same age, from the same centers. Results: After treatment, 320 women had at least one pregnancy leading to delivery after a mean of 3.35 years. Treatment significantly increased the risk of preterm delivery. Compared with no treatment, the risk of preterm birth was higher in women who had undergone treatment (33.13% vs. 6.60%). Techniques removing or ablating more tissue, such as large loop excision of the transformation zone, were associated with worse outcomes (OR 2.96, 95% IC 1.72–5.10). Smoking habits significantly increase the risk of preterm delivery in the treated women (OR 2.82, 95% IC 1.61–4.9). The risk of premature rupture of the membranes (PROM) (40% vs. 23.22%), the risk of preterm PROM (pPROM) (13.13% vs. 2.71%) and dystocic births (18.75% vs 4.48%) were also significantly increased after treatment. Caesarean sections were less frequent among the treated women (15.94% vs. 32.41%). Conclusions: Our findings reveal a relationship between cervical excisional treatment and pre-term delivery, PROM, and the method of delivery. In order to minimise risk and guarantee the best obstetric outcome, patient treatment and follow-up should be personalised.